Optimizing Circulating Tumor Cells’ Capture Efficiency of Magnetic Nanogels by Transferrin Decoration - Biglione, Catalina (2018)
Magnetic nanogels (MNGs) are designed to have all the required features for their use as highly efficient trapping materials in the challenging task of selectively capturing circulating tumor cells (CTCs) from the bloodstream. Advantageously, the discrimination of CTCs from hematological cells, which is a key factor in the capturing process, can be optimized by finely tuning the polymers used to link the targeting moiety to the MNG. We describe herein the relationship between the capturing efficiency of CTCs with overexpressed transferrin receptors and the different strategies on the polymer used as linker to decorate these MNGs with transferrin (Tf). Heterobifunctional polyethylene glycol (PEG) linkers with different molecular weights were coupled to Tf in different ratios. Optimal values over 80% CTC capture efficiency were obtained when 3 PEG linkers with a length of 8 ethylene glycol (EG) units were used, which reveals the important role of the linker in the design of a CTC-sorting system.